The Effect of Negative Brand Personality and Brand Hate on Non-Repurchase Intention With Protest Behavior as a Mediation Variable - Yasri Yasri; Muhammad Faisal (Jurnal Manajemen Universitas Bung Hatta, 2026)
This study aims to analyze the negative influence of brand personality and brand hate on non-repurchase intention, with protest behavior as a mediating variable among Oppo smartphone consumers. The population in this study was all consumers who did not intend to repurchase Oppo smartphones in West Sumatra. The research method used was descriptive quantitative, with a sample of 310 respondents. This analysis uses PLS-SEM analysis with SmartPLS 4.0. The results show a negative brand personality. has a negative and insignificant influence on protest behavior and non-repurchase intention. Brand hate has a positive and significant influence on protest behavior and a positive and significant influence on non-repurchase intention. Protest behavior has a positive and significant influence on non-repurchase intention. Protest behavior does not act as a mediator between negative brand personality and non-repurchase intention, but mediates the influence of brand hate and non-repurchase intention